Advances in business, management and entrepreneurship : proceedings of the 4th Global Conference on Business Management & Entrepreneurship (GC-BME 4), 8 August 2019, Bandung, Indonesia /: proceedings of the 4th Global Conference on Business Management & Entrepreneurship (GC-BME 4), 8 August 2019, Bandung, Indonesia. (2020) - Unknown
No abstract available